Reinforcing filler and its manufacturing method
By attaching a phosphorus-containing epoxy resin to reinforcing fibers and grinding them to a specific length, the reinforced filler effectively addresses the inefficacy and expense of existing fillers, achieving superior flame retardancy and mechanical properties when blended with resin.
Patent Information
- Application Number
- JP2023580243
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-02-09
- Filing Date
- 2023-02-06
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-02-06
AI Technical Summary
Existing reinforced fillers, such as pulverized carbon fiber reinforced plastic (CFRP), are ineffective as flame retardants due to their coarse grain and low carbon fiber content, and they are also expensive and difficult to blend with resin.
A reinforced filler is developed by attaching a phosphorus-containing epoxy resin composition to carbon fibers or other reinforcing fibers, which are then ground to a length of 20 μm or more and 10 mm or less, creating a filler that can be effectively blended with resin to provide flame retardancy in the V-0, V-1, or V-2 class of the UL standard.
The reinforced filler achieves high affinity with the resin, providing excellent flame retardancy and mechanical properties while reducing the need for additional flame retardants and being cost-effective due to the use of recycled materials.
Smart Images

Figure 0007663723000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a reinforcing filler which, when blended with a resin, can not only improve the mechanical properties but also impart flame retardancy, and a method for producing the same. [Background technology]
[0002] Examples of reinforcing fillers that are mixed into resins to impart flame retardancy include inorganic hydroxides such as aluminum hydroxide and magnesium hydroxide, as well as phosphorus compounds such as red phosphorus.
[0003] On the other hand, there is also a method of improving flame retardancy by improving thermal conductivity. For example, carbon fiber reinforced resin materials can be made flame resistant by quickly diffusing heat from flames and other sources due to the high thermal conductivity of carbon fiber.
[0004] There are reinforcing fillers called chopped and milled carbon fibers, but these have shorter fiber lengths than continuous fibers, so they must be mixed in larger amounts. However, carbon fibers with high thermal conductivity are graphitized, so they are poorly compatible with resins. In addition, they are expensive because they are made from carbon fibers.
[0005] Therefore, research is being conducted into crushing used carbon fiber reinforced plastics (CFRP) and using them as reinforcing fillers (see, for example, Patent Documents 1 and 2). As for improving compounding with resins, a method has been disclosed in which used fiber reinforced polymer materials are crushed and the crushed particles are dispersed in a base resin to obtain crushed CFRP particles terminated with epoxy functional groups (see Patent Document 3).
[0006] It is known that, in obtaining a molded article made of a thermoplastic resin, a resin composition containing fibers such as carbon fibers as a filler to improve the elastic modulus and a red phosphorus-based flame retardant to enhance flame retardancy is used (see Patent Document 4). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2006-218793 A [Patent Document 2] Patent No. 6726055 [Patent Document 3] Patent Publication No. 2021-133685 [Patent Document 4] JP 2001-131427 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, the pulverized material obtained in Patent Document 1 is an injection molded product made from long fiber pellets, and therefore the pulverized material is coarse and contains a small amount of carbon fiber, so that even if it is mixed with a resin, it has little effect as a reinforcing filler.
[0009] Furthermore, although Patent Document 2 discloses that the reinforcing filler obtained is used for flame-retardant components, this is because the reinforcing filler can contain a flame retardant, and it is not said that the reinforcing filler itself has flame retardancy.
[0010] Furthermore, in the method of Patent Document 3, the epoxy resin is applied to functionalize the crushed CFRP particles, and when the crushed CFRP particles are dispersed in a cured resin, a cured product having a network of chemically bonded crushed CFRP particles is obtained, but the cured product cannot be made flame retardant.
[0011] On the other hand, Patent Document 4 discloses a resin composition that contains a fibrous filler made of thermoplastic resin and carbon fiber and a flame retardant, and achieves flame retardancy of V-0. However, the individual materials are all separate and are mixed in a virgin state to be used as a molding resin composition, and there is no mention of using a fibrous filler as a reinforcing filler by attaching a resin containing a flame retardant to the fibrous filler in advance, or of recycling CFRP waste.
[0012] Therefore, an object of the present invention is to provide a reinforcing filler that can impart flame retardancy relatively inexpensively by using reinforcing fibers, and a method for obtaining the same. [Means for solving the problem]
[0013] That is, the gist of the present invention is as follows. (1) A reinforcing filler that can impart flame retardancy of UL standard V-0, V-1, or V-2 class by mixing with the resin to be filled, The reinforcing filler is characterized in that it contains reinforcing fibers having a fiber length of 20 μm or more and 10 mm or less, and a phosphorus-containing epoxy resin composition is adhered to at least a portion of the surface of the reinforcing fibers. (2) A reinforcing filler according to (1), wherein the phosphorus-containing epoxy resin composition contains phosphorus as a phosphorus compound, or contains phosphorus in a state in which phosphorus atoms are incorporated into a resin synthesized using a phosphorus compound. (3) The reinforcing filler according to (1) or (2), wherein the reinforcing fiber is a carbon fiber. (4) A reinforcing filler according to any one of (1) to (3), wherein the epoxy resin composition contains either a conventional phenoxy resin or an in-situ polymerization type phenoxy resin. (5) A method for producing the reinforcing filler according to any one of (1) to (4), comprising the steps of: A method for producing a reinforcing filler, comprising pulverizing a fiber-reinforced resin material having a phosphorus-containing epoxy resin composition as a matrix resin so that the fiber length of the reinforcing fibers in the fiber-reinforced resin material is 20 μm or more and 10 mm or less. (6) The method for producing a reinforcing filler according to (5), wherein the fiber-reinforced resin material in which the phosphorus-containing epoxy resin composition is used as a matrix resin is a discarded or recovered fiber-reinforced resin material. (7) A molded article obtained by blending the reinforcing filler according to any one of (1) to (4) with a resin to be filled, the molded article exhibiting flame retardancy of UL standard V-0, V-1, or V-2 class. (8) A pellet material obtained by kneading the reinforcing filler according to any one of (1) to (4) with a virgin thermoplastic resin, which is a resin to be filled. (9) A molded article obtained by using the pellet material according to (8) alone or in combination with thermoplastic resin pellets made of virgin thermoplastic resin. Effect of the Invention
[0014] The reinforcing filler of the present invention has a high affinity between the reinforcing filler and resin, making it possible to highly fill the resin to be filled (the resin to be filled). Furthermore, because the resin composition containing phosphorus is attached, the addition of new flame retardants can be reduced or eliminated when the reinforcing filler is mixed with the resin to be filled. Furthermore, the reinforcing filler of the present invention can be obtained from used fiber-reinforced resin materials as the raw material, making it inexpensive, and is environmentally friendly since no processes requiring high temperatures or organic solvents are required. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below. The reinforcing filler of the present invention is characterized in that it contains reinforcing fibers having a fiber length of 20 μm or more and 10 mm or less, and has a phosphorus-containing epoxy resin composition adhered to at least a portion of its surface, and is a reinforcing filler that can be kneaded into a resin to be filled to impart flame retardancy of UL Standard V-0, V-1, or V-2 class.
[0016] Here, the UL standard (UL94 standard) indicates the degree of flame retardancy for plastic materials such as devices and equipment (flammability test standard for plastic materials for devices and equipment), and the behavior of combustion in a specified test method is expressed by each judgment standard. In general, the order of flame retardancy is 5VA>5VB>V-0>V-1>V-2>HB, and V-2 or higher is considered to be self-extinguishing (the fire will go out when the source of fire is removed). Details of the test method, etc. are as shown in the examples described later. In the present invention, the reinforcing filler and various virgin resins were kneaded at a specified mixing ratio and pelletized, and then test pieces were obtained under specified conditions using an injection molding machine and evaluated.
[0017] The reinforcing fibers in the reinforcing filler of the present invention are suitable to be carbon fibers, glass fibers, alumina fibers, Tyranno fibers, basalt fibers, and other ceramic fibers, but are preferably carbon fibers. The type of carbon fiber may be either PAN-based carbon fiber or pitch-based carbon fiber, or a mixture of both, but most preferably only pitch-based carbon fiber, which has high thermal conductivity.
[0018] The fiber length of the reinforcing fiber is 20 μm or more and 10 mm or less. If the fiber length is less than 20 μm, it will be about the same as the filament diameter of the carbon fiber, so that the specific surface area will increase and the amount of resin composition attached to the fiber surface will decrease, resulting in a decrease in kneadability with the resin (resin to be filled) and difficulty in imparting flame retardancy. On the other hand, if the fiber length exceeds 10 mm, the fiber length and density will vary greatly due to poor fiber defibration, resulting in poor appearance and non-uniform physical properties of the molded product, which is not suitable. The fiber length is preferably 20 μm or more and 500 μm or less, and more preferably 20 μm or more and 300 μm or less.
[0019] The reinforcing filler of the present invention is characterized in that a phosphorus-containing epoxy resin composition (hereinafter, sometimes simply referred to as a resin composition) is attached to at least a part of the surface of the reinforcing fiber. Regarding the state of attachment of the resin composition, in surface observation of the reinforcing filler of the present invention using a scanning electron microscope (SEM), it is preferable that 10% or more of the surface of the reinforcing fiber is covered with the resin composition, and more preferably 50% or more is covered. In addition, the entire surface of the reinforcing fiber may be completely covered with the resin. In addition, the reinforcing filler in the present invention is intended to be mixed into the resin to be filled, which is the target of filling, in order to impart flame retardancy, and therefore exists as an aggregate of reinforcing fibers to which the resin composition is attached. Therefore, it does not matter if there are reinforcing fibers whose surfaces do not have any resin composition attached thereto, but the amount of such fibers is preferably 30 or less, and more preferably 20 or less, as a result of SEM observation of 100 randomly selected reinforcing fiber particles.
[0020] On the other hand, the amount of the resin composition attached is desirably 20 g or more and 50 g or less, and preferably 30 g or more and 40 g or less, per 100 g of the reinforcing filler. Since the adhesion rate and adhesion amount of the resin composition adhering to the reinforcing fibers are within the above-mentioned ranges, the reinforcing filler of the present invention has good compatibility with the resin to be filled, making it possible to impart good kneadability and flame retardancy, and since there is no excessive resin adhesion, it is also possible to impart thermal conductivity. The amount of resin adhesion can be measured by a combustion method, for example, by placing the reinforcing filler in a ceramic crucible and heating it in a muffle furnace at 400°C to 500°C in air for several hours to incinerate the resin, and then measuring the weight of the ash remaining in the crucible.
[0021] The epoxy resin composition (phosphorus-containing epoxy resin composition) attached to the reinforcing fiber may be either a thermosetting epoxy resin or a phenoxy resin, which is a thermoplastic resin. However, if it is a thermoplastic resin, it can be deformed by the heat during processing when it is mixed with the resin to be filled and molded, and the surface quality of the molded product can be improved and internal voids can be reduced, so it is preferably used.
[0022] Phenoxy resin, which is an epoxy resin and a thermoplastic resin, is classified into two types: conventional phenoxy resin provided in a prepolymerized state, and in-situ polymerization type phenoxy resin. In the present invention, either of these types may be used, or it may be a polymer alloy with other resins (polyamide, polycarbonate, aromatic polyester resins such as polyethylene terephthalate and polybutylene terephthalate, aromatic polyether resins such as polyether ether ketone, polyphenylene sulfide, polyolefin resins such as polypropylene and polyethylene, and their acid-modified products, styrene-acrylonitrile copolymers, and ABS resins, etc.) that mainly contain these phenoxy resins. When it is a polymer alloy, it means that the phenoxy resin is 40 wt% or more.
[0023] Furthermore, it is essential that the epoxy resin composition adhered to at least a portion of the surface of the reinforcing fiber contains phosphorus. Here, "containing phosphorus" refers to a case where the phosphorus-containing resin composition contains phosphorus as a phosphorus compound, and a case where the phosphorus atom is incorporated in a resin synthesized using a phosphorus compound. Of these, the former case is a case where phosphorus is blended in the resin composition in the form of a phosphorus compound such as red phosphorus or a phosphate ester flame retardant. The phosphorus atom exists as a compound in the epoxy resin composition separately from the epoxy resin, and is not incorporated in the epoxy resin skeleton. On the other hand, for the latter case, suitable examples include commercially available products in which phosphorus atoms are introduced into the resin skeleton, such as phosphorus-containing epoxy resin (e.g., FX-289 manufactured by Nippon Steel Chemical & Material Co., Ltd.) and phosphorus-containing phenoxy resin (e.g., ERF-001 manufactured by Nippon Steel Chemical & Material Co., Ltd.).
[0024] The phosphorus content in the resin composition attached to the surface of the reinforcing fiber is preferably 1 wt% or more and 10 wt% or less. If the phosphorus content is less than 1 wt%, the effect of imparting flame retardancy to the resin to be filled may not be sufficient, and conversely, if it exceeds 10 wt%, there is a risk of a decrease in physical properties such as the mechanical strength of the molded body. The phosphorus content is more preferably 2 wt% or more and 5 wt% or less.
[0025] The reinforcing filler of the present invention may contain non-phosphorus-containing additives, such as flame retardants such as magnesium hydroxide and antimony, nanocarbons such as carbon black, carbon nanotubes, and graphene, and nanoclays such as montmorillonite, within the scope of the invention.
[0026] Next, a method for obtaining the reinforcing filler of the present invention will be described.
[0027] The reinforcing filler of the present invention can be obtained by the following two methods. Method (1) A method in which virgin reinforcing fibers are pulverized and then coated with a phosphorus-containing epoxy resin composition or its precursor. Method (2) A method of crushing reinforcing fibers in a fiber-reinforced plastic (fiber-reinforced resin material) using a phosphorus-containing epoxy resin composition as a matrix resin to a predetermined fiber length.
[0028] [Method (1)] The reinforcing fibers used in method (1) are preferably surface-treated with a sizing agent in advance. Commercially available chopped fibers or milled fibers may also be used.
[0029] The fiber length of the reinforcing fiber is set to 20 μm or more and 10 mm or less, but the reinforcing fiber may be first coarsely crushed and then finely crushed to a predetermined fiber length. In this case, if the reinforcing fiber is in a continuous or long fiber state, it is desirable that the fiber length is cut to 50 mm or less, preferably 30 mm or less. There are no particular limitations on the crushing method, and the fiber is dry-pulverized to a predetermined fiber length using, for example, a hammer mill, a pin mill, a ball mill, a jet mill, or other device.
[0030] Next, the crushed reinforcing fibers are subjected to adhesion of resin to the fiber surface using a blender or mixer, and the phosphorus-containing resin is supplied in a state of being dissolved in a solvent or in a precursor solution while being dispersed on the crushed reinforcing fibers that are oscillated by stirring, etc. Note that the reinforcing fibers may be left in a coarsely crushed state and stirred using a blender, mixer, etc. to adhere the resin to the fiber surface, so that the fiber has a predetermined fiber length.
[0031] After the phosphorus-containing epoxy resin composition is sprayed as described above, a heat treatment is carried out as necessary to volatilize the solvent or to polymerize the resin, thereby obtaining the reinforcing filler of the present invention. The reinforcing filler may be prepared by crushing again to break up aggregated particles, or by air classification or the like to adjust the fiber length distribution.
[0032] [Method (2)] The fiber-reinforced plastic used in method (2) may be new, but from the standpoint of cost and environmental considerations, it is preferable that the fiber-reinforced plastic is a defective product or offcut that is discarded when it is manufactured as a part for office equipment such as laptops or home appliances, or that the plastic is recovered after being used as a product.
[0033] The form of the reinforcing fiber substrate used in the raw material recycled fiber reinforced plastic is not particularly limited, and a wide variety of materials can be used, including molded products and prepregs and their scraps using continuous fiber-based reinforcing fiber substrates such as unidirectional substrates and cross materials, short fiber substrates such as carbon felt, molded products molded by injection molding using fiber reinforced pellets, and spool runners generated during the injection molding of these products, etc. Recovered fiber reinforced plastics made of these reinforcing fiber substrates can be crushed so that the reinforcing fibers have a predetermined fiber length. Incidentally, recycled fiber reinforced plastics may contain various foreign matter such as paint chips, printed pieces, or inserted metal pieces on the surface, but in the present invention, carbon fiber reinforced plastic molded products containing such foreign matter can also be used.
[0034] The ratio of reinforcing fibers in general fiber reinforced plastics is in the range of about 5 to 75 wt%, but in the present invention, it is preferable to use a fiber reinforced plastic with a fiber content of 50 wt% or more as the raw material for the reinforcing filler. A small amount of reinforcing fibers in the raw material means a large resin ratio, so when used as a reinforcing filler, the effect of improving the mechanical strength of the compound, which is the resin to be filled, is small, which is not preferable.
[0035] In the method (2) for producing the reinforcing filler, the raw material, recycled fiber-reinforced plastic, is first coarsely pulverized. The method for coarsely pulverizing is not particularly limited, but for example, a cutter mill, a crusher mill, a hammer mill, or other device is used to produce pulverized pieces of fiber-reinforced plastic. In addition, prepregs and the like may be hardened in advance to make them easier to crush, or may be subjected to a separate pre-treatment such as freezing to make them easier to crush.
[0036] Next, the crushed pieces of fiber-reinforced plastic are finely pulverized using a pulverizer capable of fine pulverization until the fiber length of the reinforcing fibers is 10 mm or less, thereby obtaining a reinforcing filler. The method of fine pulverization is not particularly limited, and may be performed using the same equipment as for coarse pulverization, but it is preferable to use a ball mill or a jet mill. However, in this fine pulverization, the fiber length of the reinforcing fibers is set to 20 μm or more. The reinforcing filler may retain the structure of the reinforcing fiber base material of the recycled fiber reinforced plastic that is the raw material.
[0037] If necessary, the reinforcing filler thus obtained may be subjected to magnetic separation or a method utilizing density differences to remove resin powder and metal components, or may be subjected to classification or the like to adjust the fiber length distribution.
[0038] The reinforcing filler of the present invention is used by blending it as is with the resin to be filled, but the compound may be processed as it is into a molded article using a hot press, or it may be pelletized and then processed into a molded article by injection molding or the like.
[0039] Pelletization is carried out using a normal extruder. In this case, it is preferable to use crushed pieces having a size of 3 mm or more, and more preferably, crushed pieces having a size of 5 to 10 mm. If the size of the crushed pieces is smaller than 3 mm, they will not be easily caught when pelletized by the extruder, and if the size of the crushed pieces is larger than 10 mm, the fiber length and density may vary greatly due to poor fiber defibration.
[0040] In pelletizing, a thermoplastic resin to be mixed with the reinforcing filler of the present invention may be used. Examples of the thermoplastic resin include olefin resin, polyamide (PA), polycarbonate (PC), polyester, polyarylene sulfide, polyamideimide, polyetherimide, polyethersulfone, polyphenylene ether and its modified products, polyphenylene sulfide, polyoxymethylene, polyarylate, polyether ketone (PEK), polyether ether ketone (PEEK), polyether ketone ketone, and vinyl chloride. Examples of the olefin resin include polyethylene (PE) and polypropylene (PP). Modified polyolefins can also be used. The modified polyolefins are not particularly limited as long as they are polyolefins modified to give polarity, and examples of the modified polyolefins include polyolefins modified with (anhydrous) carboxylic acid, epoxide, oxazoline, isocyanate, carbodiimide, and the like. The polyolefins may be hydrogenated. One or more types of the thermoplastic resin may be used, and any resin that has affinity with the matrix resin of the fiber-reinforced plastic that is the raw material of the reinforcing filler is suitable. It is preferable that the resin has a similar chemical structure, and more preferably that the resin is the same type.
[0041] The pellets can be used alone, but it is preferable to mix them with virgin resin or fiber thermoplastic resin pellets and mold them into a desired molded body using an injection molding machine. When mixing with virgin resin or fiber thermoplastic resin pellets, it is preferable to set the mixing ratio of pellets (A) in the range of 30 wt% or more and less than 80 wt% when the total amount of pellets (A) using the reinforcing filler of the present invention and pellets (B) not containing the reinforcing filler of the present invention is 100 parts by weight, and it is preferable to adjust the mixing ratio of pellets (A) to 40 wt% or more and 70 wt% or less. If the mixing ratio of pellets (A) is less than 30 wt%, it is not possible to impart flame retardancy of V-2 or more to the molded body, and if the mixing ratio is 80 wt% or more, injection molding becomes difficult due to insufficient resin fluidity. The type of virgin resin or matrix resin of the fiber-reinforced thermoplastic resin pellets to be mixed with the pellets is not particularly limited as long as it has affinity with the matrix resin of the fiber-reinforced plastic, which is the raw material of the reinforcing filler, but it is preferably one with a similar chemical structure, and more preferably the same type of resin.
[0042] In producing a molded body, in addition to the reinforcing filler and virgin resin of the present invention, it is possible to add plasticizers for binder resins, adhesion improvers, compatibilizers, dispersants for recycled filler particles, heat stabilizers, foaming agents, colorants, lubricants, antistatic agents, other inorganic or organic fillers, flame retardants, flame retardants, surfactants, mold release agents, thickening stabilizers, etc. These may be used alone or in combination of two or more.
[0043] Molded articles obtained using the reinforcing filler of the present invention can be used in a wide range of fields, including applications such as housings for information devices, primarily laptop computers, and housings for mobile phones that require high rigidity and high EMI shielding properties, as well as building materials, and structural materials for aircraft, railway vehicles, and automobiles. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples as long as the gist of the present invention is not exceeded. The evaluations used in the following examples were performed according to the following methods.
[0045] [Resin adhesion amount] 5 g of the reinforcing filler was placed in a pre-weighed ceramic crucible, and its weight was measured using an electronic balance. It was then ignited in a muffle furnace at 450°C for 12 hours, cooled to room temperature in a desiccator, and then its weight was measured using the electronic balance. The weight loss before and after ignition was calculated as the amount of resin.
[0046] [Mechanical strength] The bending strength and elastic modulus of the molded body were measured based on JIS K 7074 Bending test method for carbon fiber reinforced plastics.
[0047] [Flame retardant] The evaluation was conducted in accordance with the vertical flame test (94V-0) specified in UL94 of the US UL standard, using test pieces measuring 125 mm in length, 13 mm in width, and 3.0 mm in thickness.
[0048] Example 1 Carbon fiber reinforced plastic (carbon fiber weight content 59.5wt%, phosphorus flame retardant weight content 1.2wt%, molded product density 1.64g / cm) molded from in-situ polymerization type phenoxy resin prepreg containing phosphorus flame retardant (NS-TEPreg flame retardant type manufactured by Nippon Steel Chemical & Material Co., Ltd.) 3 ) was coarsely crushed using a cutter mill, and the resulting coarsely crushed product was then crushed using a ball mill and screened to obtain reinforcing fillers having a shape (size) of 5 mm to 10 mm.
[0049] 30 parts by mass of the obtained reinforcing filler was mixed with 70 parts by mass of phenoxy resin (YP-50S, manufactured by Nippon Steel Chemical & Material Co., Ltd.), which is the resin to be filled, using a twin-screw extruder, then pelletized. Using a 100-ton injection molding machine, a multipurpose test piece type A1 conforming to JIS K7139 was produced at a cylinder temperature of 180°C, an injection pressure of 15MPa, and a mold temperature of 30°C, and bending properties were evaluated. In addition, a test piece 125 mm long, 13 mm wide, and 3.0 mm thick was produced under the same molding conditions, and a UL94V test was performed in accordance with the UL94V combustion test standard. The results are shown in Table 1.
[0050] (Examples 2 and 3) Test pieces were prepared and evaluated in the same manner as in Example 1, except that the mixing ratio of the reinforcing filler and the phenoxy resin was changed to the conditions shown in Table 1. The results are shown in Table 1.
[0051] Example 4 30 parts by mass of the reinforcing filler obtained in the same manner as in Example 1 was mixed with 70 parts by mass of polyphenylene sulfide resin (PPS, Toray Torelina A900) as the resin to be filled, using a twin-screw extruder, and then pelletized. A multipurpose test piece type A1 conforming to JIS K7139 was produced using a 100-ton injection molding machine at a cylinder temperature of 300°C, an injection pressure of 15MPa, and a mold temperature of 150°C, and bending properties were evaluated. In addition, a test piece with a length of 125 mm, a width of 13 mm, and a thickness of 3.0 mm was produced under the same molding conditions, and a UL94V test was performed in accordance with the UL94V combustion test standard. The results are shown in Table 1.
[0052] Example 5 30 parts by mass of the reinforcing filler obtained in the same manner as in Example 1 was mixed with 70 parts by mass of polypropylene resin (PP, Sunallomer PM600A manufactured by Sunallomer) as the resin to be filled, using a twin-screw extruder, and then pelletized. A multipurpose test piece type A1 conforming to JIS K7139 was produced using a 100-ton injection molding machine at a cylinder temperature of 210°C, an injection pressure of 35 MPa, and a mold temperature of 45°C, and bending properties were evaluated. In addition, a test piece with a length of 125 mm, a width of 13 mm, and a thickness of 3.0 mm was produced under the same molding conditions, and a UL94V test was performed in accordance with the UL94V combustion test standard. The results are shown in Table 1.
[0053] [Comparative Example 1] Molded bodies (multipurpose test piece type A1 and test pieces) were prepared in the same manner as in Example 1, except that chopped fiber (pitch-based carbon fiber XN-80, fiber length 12 mm, manufactured by Nippon Graphite Fiber Co., Ltd.) was used instead of the reinforcing filler, and various evaluations were carried out. The results are shown in Table 1. In Table 1, the evaluation of flame retardancy "x" indicates that there is no self-extinguishing property.
[0054] [Table 1]
[0055] As shown in Table 1, the reinforcing filler of the present invention can impart flame retardancy to the resin to be filled, and a molded article with excellent mechanical properties can be obtained by blending it with the resin to be filled. Furthermore, according to the present invention, the fiber-reinforced plastic can be recycled as a molded article again.
Claims
1. A reinforcing filler that can impart flame retardancy of UL standard V-0, V-1, or V-2 class by mixing with the resin to be filled, The reinforcing filler is characterized in that it contains reinforcing fibers having a fiber length of 20 μm or more and 10 mm or less, and a phosphorus-containing epoxy resin composition is adhered to at least a portion of the surface of the reinforcing fibers in an amount of 20 g or more and 50 g or less per 100 g of the reinforcing filler.
2. 2. The reinforcing filler according to claim 1, wherein the phosphorus-containing epoxy resin composition contains phosphorus as a phosphorus compound, or contains phosphorus in a state in which phosphorus atoms are incorporated into a resin synthesized using a phosphorus compound.
3. 2. The reinforcing filler according to claim 1, wherein said reinforcing fibers are carbon fibers.
4. 2. The reinforcing filler of claim 1, wherein the epoxy-based resin composition comprises either a conventional phenoxy resin or an in situ polymerized phenoxy resin.
5. A method for producing the reinforcing filler according to any one of claims 1 to 4, comprising the steps of: A method for producing a reinforcing filler, comprising pulverizing a fiber-reinforced resin material having a phosphorus-containing epoxy resin composition as a matrix resin so that the fiber length of the reinforcing fibers in the fiber-reinforced resin material is 20 μm or more and 10 mm or less.
6. 6. The method for producing a reinforcing filler according to claim 5, wherein the fiber-reinforced resin material having a phosphorus-containing epoxy resin composition as a matrix resin is a discarded or recovered fiber-reinforced resin material.
7. A molded article obtained by blending the reinforcing filler according to any one of claims 1 to 4 with a resin to be filled, and exhibiting flame retardancy of UL standard V-0, V-1 or V-2 class.
8. A pellet material obtained by kneading the reinforcing filler according to any one of claims 1 to 4 with a virgin thermoplastic resin which is a resin to be filled.
9. A molded article produced by using the pellet material according to claim 8 alone or in combination with thermoplastic resin pellets made of virgin thermoplastic resin.
Citation Information
Patent Citations
Production of glass fiber bundle for reinforcing polyphenylene sulfide and resin body
JP1990160646A
Thermoplastic resin composition
JP2001131427A
Method for recycling carbon fiber-reinforced thermoplastic resin molding
JP2006218793A
Resin for adhesive, and FRP resin containing the same
JP2007045957A
Flame-retardant carbon fiber-reinforced composite material and method for producing the same
JP2007231073A